Modeling dust in a universe of galaxies. Issue Volume 15:Issue S352(2019) (June 2019) - Narayanan, Desika; Li, Qi; Davé, Romeel; Conroy, Charlie; Johnson, Benjamin D.; Popping, Gergo
Abstract: In this invited talk, we discuss the physics of the lifecycle of dust in the context of galaxy formation simulations. After outlining the basic physical processes, we apply algorithms for the formation, growth, and destruction of dust in the ISM to a state-of-the-art cosmological simulation to develop a model for the evolution of the dust to gas and dust to metals ratios in galaxies. We show that while modern simulations are able to match the observed dust mass function at redshift z = 0, most models underpredict the observed mass function at high-redshift ( z = 2). We then show the power of these techniques by expanding our model to include a spectrum of dust sizes, and make initial predictions for extinction laws in local galaxies.